A series of MOFs based on a triangular tri(4-pyridylphenyl)amine ligand combined with carboxylate or nitrate auxiliary ligands12. Issue 3 (26th November 2014) - Meng, Fandian; Zhang, Mingdao; Shen, Kang; Li, Yizhi; Zheng, Hegen
Abstract : A series of new metal–organic frameworks based on a triangular tri(4-pyridylphenyl)amine (TPPA) ligand that possess novel structures and features have been successfully synthesized and structurally characterized in detail. Abstract : A series of new metal–organic frameworks (MOFs) based on a triangular tri(4-pyridylphenyl)amine (TPPA) ligand that possess novel structures and features, namely [Co2 (TPPA)2 (1, 3-bdc)2 (H2 O)] n (1 ); [Zn(TPPA)(1, 3-bdc)] n (2 ); [Zn6 (TPPA)2 (betc)(Hbetc)2 (H2 betc)(H2 O)6 ·7H2 O·2DMA] n (3 ) and [Cu(TPPA)(NO3 )2 (H2 O)]·2H2 O] n (4 ) (1, 3-H2 bdc = 1, 3-benzenedicarboxylic acid, betc = 1, 2, 4, 5-benzenetetracarboxylic dianhydride), have been synthesized under solvothermal conditions. In our work different MOFs were synthesized from different metal ions and in different solvents, leading to a variety of coordination modes and structures. In addition, the photochemical properties of compounds1–4 and the ligands in the solid state were studied.